2017
DOI: 10.20965/jdr.2017.p0593
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bridge Inspection Support System Using Two-Wheeled Multicopter and 3D Modeling Technology

Abstract: Recently, many countries have faced serious problems associated with aging civil infrastructures such as bridges, tunnels, dams, highways and so on. Aging infrastructures are increasing year by year and suitable maintenance actions are necessary to maintain their safety and serviceability. In fact, infrastructure deterioration has caused serious problems in the past. In order to prevent accidents with civil infrastructures, supervisors must spend a lot of money to maintain the safe conditions of infrastructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…360°cameras are readily accessible, but their use for bridge management is relatively unexplored, with only a few studies reported (e.g. Nishimura et al 2012, Hada et al 2017, Humpe 2020.…”
Section: °Camerasmentioning
confidence: 99%
“…360°cameras are readily accessible, but their use for bridge management is relatively unexplored, with only a few studies reported (e.g. Nishimura et al 2012, Hada et al 2017, Humpe 2020.…”
Section: °Camerasmentioning
confidence: 99%
“…Similar conclusions were drawn by Koch et al [8] after analysing different large concrete structures (Figure 1). Many efforts are being successfully made to improve the quality and autonomy of UAS-enabled bridge inspections [9][10][11][12][13][14]. Nevertheless, a systematic methodology for inspections is needed to improve the overall quality of bridge inspections.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the lack of information and to make the available information easier to understand, it is also important to systematize data collection when viewing the images. A clear and systematized protocol using UAV for bridge inspection is also Many efforts are being successfully made to improve the quality and autonomy of UAS-enabled bridge inspections [9][10][11][12][13][14]. Nevertheless, a systematic methodology for inspections is needed to improve the overall quality of bridge inspections.…”
Section: Introductionmentioning
confidence: 99%
“…T diversity of desired missions and associated requirements for multicopter Unmanned Air Vehicles (UAVs) is expanding rapidly. Their utility primarily lies in their agile flight and hovering capabilities, which makes them adept at inspection [1,2], delivery [3], retrieval, and interacting closely with their environment [4]. The energy and power requirements needed to enable this, however, are also a major weakness.…”
Section: Introductionmentioning
confidence: 99%